THE EFFECT OF ROLE PLAY TECHNIQUE ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 29 PEKANBARU - Marisa Risdayanti; Eliwarti '; M Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This pre-experimental research is aimed to find out the effect of Role Play technique on the speaking ability of the second year students of SMPN 29 Pekanbaru. The research data were collected from April to May 2016. The subject of this research was class VIII.1 which consist of 43 students. The data were collected by giving a pre-test and a post-test to the students in the form of limited picture-cued task. The data were assesed by the three raters and then analyzed using SPSS 16.0. The result of the research showed that the increase of mean score from the pre-test to the post-test was 11.79 where the score of the pre-test was 52.07 and the score of the post test was 63.86. And the result of t-obs was 19.820, mean-while the t-table values was 2,018. Therefore, it can be concluded that Role Play technique gives positive effects to the students’ speaking ability.Keywords: Role Play, Speaking Ability